Establishing relational responding in accordance with more-than and less-than as generalized operant behavior in young children - Paul Strand (International Journal of Psychology and Psychological Therapy, 2004)
The current study constitutes the first attempt to generate repertoires of relationalresponding, as generalized operant behaviors, when they are found to be absent inyoung children, using interventions suggested by Relational Frame Theory. Threechildren, aged between 4 and 6 years, were exposed to a basic problem-solving taskthat involved two or three identically-sized paper coins in an attempt to test andtrain patterns of relational responding in accordance with more-than and less-than.On each trial, the experimenter described how the coins compared to one anotherin terms of their value, and the child was then asked to pick the coin that wouldbuy as many sweets as possible. All three participants failed to pass baseline testsfor specific patterns of arbitrary more and less responding. Interventions suggestedby Relational Frame Theory, including training and testing across stimulus sets,were then successfully used to establish increasingly complex patterns of relationalresponding in all three children. Generalization tests demonstrated that the relationalresponding successfully generalized to novel stimuli and to a novel experimenter.In addition, the use of a non-contingent reinforcement condition for one participant,during which no improvement was made, together with contingency reversals forall children, indicated that the trained and tested relational responding may beconsidered a form of generalized operant behavior. These findings lend positivesupport to Relational Frame Theorys approach to derived relational responding,and to the functional analysis of human language and cognition. Alternativeinterpretations of the data are also considered.